E-government as an innovative mechanism of cooperation between government, business and civil society: international experience and background of development in Ukraine - S. A. Kvitka; O. O. Sokolovs’ka (Aspekti Publìčnogo Upravlìnnâ, 2015)
The article examines the experience of implementation and operation of e-government in foreign countries in the context of its possible use in Ukraine. We consider the definition of «electronic government.» The article shows the trend of increasing the number of countries using e-technology in public administration. Attention is drawn to the problems that arise on the way to implementing e-government in state and local government in Ukraine. Also, the author considered the main problem to be solved in the process of creation and gradual implementation of information system «Electronic Government».